Localization of 113mIn- and 67Ga-Labeled Poly-methylene-Phosphonates in Myocardial Infarct - Mrinal, Dewanjee K. (Nuklearmedizin - NuclearMedicine, 1977)
We have investigated the usefulness of two new 67Ga-chelates, i. e. 67Ga-ethylene diamine tetramethylenephosphonate (67Ga-EDTMP) and 67Ga-diethylenetriamine pentamethylene phosphonate (67Ga-DTPMP), and of two 113mIn-chelates, i. e. 113mIn-EDTMP and 113mIn-DTPMP, for imaging myocardial infarct in rabbits. The agents were prepared by adding 113mIn3+ or 67GaCl4– ion to 20–50 mg of EDTMP or DTPMP stock solution and neutralizing to pH of 7.4. Myocardial infarcts were introduced into 15 rabbits by ligation of the left anterior descending coronary artery. The rabbits were then injected with a mixture of 113mIn-EDTMP, 45Ca-EDTMP or 67Ga-EDTMP and corresponding DTPMP chelates. The radioactivity-mapping of the heart was made by removing the outer and inner layers of pale or hemorrhagic infarct. Beta and gamma radioactivity in the heart and other tissue samples were obtained. There was excellent correlation between the radioactivity distribution of the 45Ca- and 113mIn-chelates. The predominant concentration was in the bones, bladder, kidney and infarcted myocardium. For 113mIn-EDTMP, an average ratio of 30 :1 between infarcted and normal myocardium (IM/NM) was obtained at 24 hrs after ligation. This ratio peaked 48 hrs after ligation to 50:1. For 6 7Ga-EDTMP this ratio varied from (7–10): 1. The blood clearance 67Ga-EDTMP was slow. Gel filtration of serum containing 113mIn-EDTMP and 67Ga-EDTMP showed that 45% and 86% of the radioactivity were protein bound. We observed that protein binding of metal chelates is an important characteristic for localization in myocardial infarct. The two pairs of 113mIn-EDTMP and 201T1+ ion or 67Ga-EDTMP and 13NH4+ ion should be useful for multiple imaging of myocardial infarct with the gamma or positron camera, respectively.